Radiographic Evaluation of Bioglass and Polymethylmethacrylate for Long Bone Fracture Repair in Dogs - Sawant, Rutuja; Yadav, Girish; Lokhande, Dinesh; Khandekar, Gajendra; Patil, Harshal; Saini , Dishant (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Long bone fracture fixation with various techniques, viz., internal fixation, external fixation, external coaptation has been adapted since long time in veterinary practice. Despite of such advancements complications like implant loosening, migration resulting in malunion, non-union and delayed union are being observed later on. Various biomaterials have been identified and used in fracture management to improve the implant stability by holding bone and implant in position, enhancing and accelerating the bone healing via callus formation. Bioglass and Polymethylmethacrylate (PMMA) bone cement are a few of the biomaterials being used in the veterinary orthopaedics. This study was conducted on clinical cases of long bone fracture repair in 12 dogs, divided equality into two groups. Group I dogs were treated with Locking Compression Plate with bioglass putty as filling agent at interfragmentary spaces, while those in Group II were treated with Locking Compression Plate with PMMA as filling agent at interfragmentary spaces. The bone formation and bone union scores were significantly improved at 15th, 30th and 60th day interval of observation in both the groups. There was no statistically significant difference in scores between two groups, yet the scores were found to be better in group I, which might be attributed to the osteostimulative and osteoconductive properties of bioglass bone cement. PMMA bone cement is non-biodegradable and has numerous potential uses, but has serious disadvantages due to its adverse effects also